Shock-wave lithotripsy, ureterorenoscopy and percutaneous nephrolithotomy for 1–2 cm renal stones: A randomised pilot study. (November 2020) - McCahy, Philip J; Hong, Matthew; Paul, Eldho; Berman, Ivor; Shahbaz, Shekib
Objectives: This study aimed to assess which of extracorporeal shock-wave lithotripsy (SWL), ureterorenoscopy (URS) or percutaneous nephrolithotomy (PCNL) offers the best stone-free rate (SFR) for 1–2 cm renal stones. Patients and methods: A total of 31 patients with renal stones between 1 and 2 cm were randomised to SWL, URS or PCNL. Repeat treatments or alternatives were performed until the patient was stone free or clinically in no further need of treatment. All patients were assessed with computed tomography scanning independently reviewed by a radiologist blinded to the treatment. Results: Overall, 10 well-matched patients were randomised to SWL, 11 to URS and 10 to PCNL. SFRs were 60% for SWL, 55% for URS and 80% for PCNL (no significant difference). The mean number of procedures required were 2.6 (range 1–7) for SWL, 2.5 (range 1–4) for URS and 1.3 (range 1–3) for PCNL ( p =0.072). There were no major complications, but 50% of SWL had minor complications compared with 9% for URS and 20% for PCNL. Conclusion: The results for SWL were disappointing for SFR, number of procedures and complications. In common with other recent studies, the SFR following URS was also poor. PCNL had the best results for SFR with the fewest procedures. We calculate that an adequately powered study will require 42 patients per arm. Level of evidence: Level 2b